Komparansi Metode Pembelajaran Pendidikan Agama Kristen dalam Perspektif Alkitab Perjanjian Lama dan Perjanjian Baru: Riset ini bertujuan buat menggali serta menganalisis metode- metode pendidikan yang diajarkan dalam Alkitab, dan mengeksplorasi relevansinya untuk pembelajaran agama Kristen masa saat ini - Bincar Haposan Sibarani (Ra'ah: Journal of Sociology of Religion, 2024)
The purpose of this research is to conduct a comparative analysis of the methods used in Christian Religious Education based on biblical texts, particularly from the perspectives of the Old Testament and the New Testament. The Bible, as the primary source of Christian faith teachings, contains various narratives and instructions that reflect different pedagogical approaches during each period. In the Old Testament, teaching methods were generally conveyed through laws, commandments, ritual symbols, and narrative stories. The media used included oral instruction, symbolic tools (such as the Ark of the Covenant and the altar), and communal experiences. Meanwhile, in the New Testament, teaching methods emphasized narrative approaches through parables, direct teaching by Jesus Christ, and the role of the Holy Spirit as the teacher within the hearts of believers. The media used in the New Testament included apostolic writings, letters, and the church community as channels for transmitting doctrine. Christian Religious Education teachers, as the front line in imparting moral and ethical values, are also required to creatively package the learning process using various methods and teaching media, ensuring that the message is easily understood by students.